Ultrasound-assisted enhancement of bioactive compounds in hawthorn vinegar: A functional approach to anticancer and antidiabetic effects - Selim Öğüt; Melikenur Türkol; Seydi Yıkmış; Esra Bozgeyik; Gholamreza Abdi; Emine Kocyigit; Rana Muhammad Aadil; Nilay Seyidoglu; Deniz Karakçı; Nazlı Tokatlı (Ultrasonics Sonochemistry)
In this study, the effects of ultrasound treatment on bioactive components and functional properties of hawthorn vinegar (Crataegus tanacetifolia) were investigated. Parameters such as total phenolic compound (TPC), total flavonoid content (TFC), ascorbic acid (AA), DPPH radical scavenging activity and CUPRAC reducing capacity were optimised by surface response method (RSM) and 14 min duration and 61.40 % amplitude were determined as the most suitable treatment conditions. The results showed that ultrasound treatment improved the antioxidant properties of hawthorn vinegar by increasing TPC, TFC, DPPH and CUPRAC values. In addition, it was observed that hawthorn vinegar samples exhibited anticancer effects in cell culture experiments. In experiments on A549 (lung), MCF-7 (breast) and HT-29 (colon) cancer cell lines, ultrasound-treated vinegar increased apoptotic effects, suppressed cell migration and reduced necrosis rates in some cell lines. In particular, ultrasound treatment of vinegar resulted in a reduction in the expression of anti-apoptotic genes (BCL-2 and XIAP) and an enhancement in the expression of pro-apoptotic genes (BAX). These findings suggest that ultrasound technology preserves and enhances the bioactive components of hawthorn vinegar, improves its anticancer properties and increases its potential for use as a functional food product.